Latent profile analysis of professional identity and its correlation with humanistic practice competence in undergraduate nursing interns - Xu, Shuqin; Gao, Yuanyuan; Zou, Yixun; Shen, Jingying; Zhu, Aiyong; Zhao, Chong; Zhou, Qianqian (Frontiers in Medicine, 2025)
IntroductionNursing professional identity is a key predictor of clinical performance and career development among nursing interns, with its heterogeneity being particularly pronounced during clinical placements. Current research often overlooks subgroup differences and lacks exploration of the mechanisms linking nursing professional identity to humanistic practice competence, which hampers the development of targeted educational strategies. This study aims to identify and explore the latent categories and characteristics of professional identity among interns, analyze influencing factors across different categories, and provide references for developing targeted nursing education interventions.MethodsUsing convenience sampling, 295 undergraduate nursing interns from Shanghai University of Medicine & Health Sciences were surveyed between December 2023 and April 2025. The investigation utilized a general information questionnaire, the Nurse Professional Identity Scale, the Nurse Humanistic Practice Competence Assessment Scale. Latent profile analysis was employed to identify potential categories of professional identity, and logistic regression analysis was used to determine its influencing factors.ResultsProfessional identity was categorized into three latent profiles: low-level group (35.25%), moderate-level group (49.50%), and high-level group (15.25%). Multivariate analysis revealed that current appreciation for the nursing profession, reasons for choosing nursing as major (parental advice), self-management ability, and ethical and legal practice ability were significant predictors of professional identity levels (p < 0.05).DiscussionThe professional identity of nursing interns is heterogeneous, with the majority categorized at moderate or low levels. Personal attitudes and core competencies are key influencing factors. Educators should implement stratified interventions based on the three identified profiles: For the low-level group, enhance emotional support and foster professional identity through narrative pedagogy and micro-goal mentoring. For the moderate-level group, boost reflective practice and intrinsic motivation via structured volunteer-clinical linkages. For the high-level group, promote sustained development through research innovation and dual mentorship. Furthermore, integrating self-management and ethical practice training into the curriculum, along with pre-admission career experience programs, is recommended to effectively enhance professional identity and humanistic practice competence.